Anak Berkebutuhan Khusus dalam Perspektif Psikologi Pendidikan Islam - Halmianto Halmianto; Siti Rokhimah (TSAQOFAH, 2026)
Although the issue of children with special needs (ABK) has received attention in various studies of psychology and education, discussions that specifically examine the understanding and support of ABK from the perspective of Islamic educational psychology with a holistic-spiritual approach remain limited. This study aims to analyze the concept of Islamic educational psychology in understanding the characteristics, needs, and appropriate support strategies for ABK, as well as to integrate them with the principles of Islamic values. This study used a qualitative approach with a library research design. Data were obtained from various primary and secondary literature, such as books of Qur’anic exegesis, hadith, books on Islamic psychology, accredited national and international journals, and other relevant academic sources, selected through purposive sampling based on topic relevance, source credibility, and publication period. Data were collected through documentation and analyzed using content analysis with the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results showed that Islamic educational psychology views ABK as individuals who possess fitrah, or innate potential, that needs to be developed, rather than as weak or helpless persons. This approach emphasizes five main principles, namely tawhid, compassion (rahmah), patience, justice in treatment and access to education, and a holistic approach that integrates physical, spiritual, and intellectual aspects. The recommended support strategies include guidance based on noble character, spiritual strengthening through worship and prayer, and the adaptation of learning methods that are friendly and responsive to children’s special conditions. The conclusion of this study affirms the importance of internalizing spiritual values and a holistic-integrated approach in the education and support of ABK within both families and Islamic educational institutions. The implications of this study include theoretical contributions to the development of literature on Islamic educational psychology and inclusive education, as well as practical implications for Islamic educational institutions, teachers, parents, and policymakers in formulating learning that is more humanistic, religious, adaptive, and oriented toward the needs of ABK.